2021
DOI: 10.1016/j.jare.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide inhibits aortic valve calcification in heart via regulating RUNX2 by NF-κB, a link between inflammation and mineralization

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 47 publications
4
30
0
Order By: Relevance
“…Recently, a link between inflammation and calcification has been suggested via regulating RUNX2 by nuclear factor kappa B (NF-κB) [ 51 ]. NF-κB is one of the main mediators of inflammation that plays a crucial role in the initiation and progression of CAVD [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a link between inflammation and calcification has been suggested via regulating RUNX2 by nuclear factor kappa B (NF-κB) [ 51 ]. NF-κB is one of the main mediators of inflammation that plays a crucial role in the initiation and progression of CAVD [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cells appear before calcium nodules in the aortic valve, and inflammatory cells are subject to localize around calcific nodules (Abdelbaky et al 2015 ; Coté et al 2013 ). Multiple studies have found that the NF-kB signaling pathway is an important one that regulates the pro-inflammatory response, and it is closely associated with the development of CAVD (Éva Sikura et al 2021 ; Liu et al 2017 ; Zeng et al 2017 ). Our study found that PM induced AVICs to differentiate into osteoblast-like phenotype, thereby secreting more inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the ATP undersupply, the calcium pump within cardiomyocytes cannot effectively remove calcium from the cytoplasm, resulting into calcium overload [40,41]. The resultant abnormal calcium signal blunts ventricular contraction and promotes the development of cardiac dysfunction [42][43][44].…”
Section: Overview Of Myocardial I/r Injurymentioning
confidence: 99%